Presence of pharmaceuticals in the Lis river (Portugal): Sources, fate and seasonal variation - Paíga, Paula (2016)
The occurrence of 33 pharmaceuticals and metaboliteswas evaluated along the Lis river and in the influents and effluents of twowastewater treatment plants (WWTPs) located along the river. Results indicate that pharmaceuticals, such as ibuprofen, ketoprofen, carbamazepine and fluoxetine, and the metabolite salicylic acid are widespread along the Lis river, showing 100% of detection frequency, at levels up to 1.3 μg L–1. The number of molecules detected increased along the river, with 11 molecules in the source, 15 upstreamWWTP 1, 16 downstreamWWTP 1 and upstreamWWTP 2 and 19 downstream WWTP 2. The highest concentrations were often found downstream near the river mouth. Different possible sources of contamination of the Lis river were identified, namelyWWTP effluents, untreated wastewaters and livestock production. Nevertheless, the discharge of WWTP effluents appeared to be the most pronounced, given that, in general, it was noticed an increase in the concentration of pharmaceuticals downstream of the WWTPs. WWTP effluents contributed with a total mass load of pharmaceuticals into the Lis river between 470 and 2317 mg/d/1000 inhabitants. Non-steroidal anti-inflammatory drugs/analgesics were the therapeutic groupwith a high contribution to the total mass load of pharmaceuticals entering the Lis river, followed by psychiatric drugs and antibiotics. No seasonal variation was observed for the detected concentrations of pharmaceuticals. At the levels detected in the Lis river, sulfamethoxazole, clarithromycin, azithromycin and ibuprofen showed to have potential risk for aquatic organisms. These findings show that further studies embracing different environmental compartments (water, sediment and biota) are needed, in order to evaluate the partition/distribution of pharmaceuticals, their metabolites and transformation products in the environment aswell as to predict their possible impact to non-target organisms and, in a last instance, to human health.